Agrocom invites elite investment in horticulture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Interprofessional Association of Agriculture, Agro-industry and Communication (known as Agrocom) was set up as a registered public utility on 24 November 1994 in Douala (Cameroon). Its goal is to organise the non-traditional sectors involved in...